Novel glyproline GZK-111 with neuropsychotropic activity - K. N. Koliasnikova; A. G. Alyaeva; E. A. Kuznetsova (LLC "Publisher OKI", 2022)
Thе article represents a review of our own researches, which describes the design, synthesis and pharmacological properties of linear substituted glyproline GZK-111, a potential drug for the complex treatment of psychiatric pathologies, including anxiety, depressive disorders, and cognitive impairment. The relationship between structure and activity in a series of this glyproline analogs is described. The experimental evidence of the GZK-111 ability to metabolized with the formation of cycloprolylglycine, which is identical to the endogenous cyclic dipeptide, is presented. The data on toxicological and pharmacokinetic studies of GZK-111 are presented.